2013
DOI: 10.1254/jphs.13042fp
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effects of ZSET1446/ST101 With Memantine on Cognitive Function and Extracellular Acetylcholine in the Hippocampus

Abstract: Abstract. In the novel object recognition task, ZSET1446 (also coded as ST101) enhanced object recognition memory in mice and ameliorated cognitive impairment caused by scopolamine in rats. The enhancement induced by ZSET1446 in mice was abolished by injection of mechamylamine, a nonselective antagonist of nicotinic acetylcholine (ACh) receptors, or dihydro-berythroidine, a selective antagonist against the a4 subunit of nicotinic ACh receptors. These results suggest that the procognitive effect of ZSET146 is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Moreover, in the radial maze test, the acute intraperitoneal injection of 0.3 and 0.56 mg/kg of memantine 20 minutes prior to the acquisition reduced the error and improved memory in the memory recall test (18 hours after the last acquisition session) ( Wise & Lichtman, 2007 ). It seems that memantine affects memory enhancement in these cases through the imbalance between GABAergic and glutamatergic functions and higher levels of extracellular acetylcholine ( Drever et al, 2007 ; Ihalainen et al, 2011 ; Povysheva & Johnson, 2016 ; Shearman et al, 2006 ; Yamaguchi et al, 2013 ). Also, the differences in the effective amount of memantine are related to the treatment method (oral and intraperitoneal), the duration of treatment (acute and chronic), and the treatment time (before training, immediately after training, and before recalling).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the radial maze test, the acute intraperitoneal injection of 0.3 and 0.56 mg/kg of memantine 20 minutes prior to the acquisition reduced the error and improved memory in the memory recall test (18 hours after the last acquisition session) ( Wise & Lichtman, 2007 ). It seems that memantine affects memory enhancement in these cases through the imbalance between GABAergic and glutamatergic functions and higher levels of extracellular acetylcholine ( Drever et al, 2007 ; Ihalainen et al, 2011 ; Povysheva & Johnson, 2016 ; Shearman et al, 2006 ; Yamaguchi et al, 2013 ). Also, the differences in the effective amount of memantine are related to the treatment method (oral and intraperitoneal), the duration of treatment (acute and chronic), and the treatment time (before training, immediately after training, and before recalling).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study suggests that coapplication of ZSET1446 and the NMDA receptor antagonist memantine has a positive effect on cognitive functions in mice and rats. An increase in the extracellular levels of ACh in the hippocampus was observed upon application of this compound [149,150]. It was also demonstrated that a7 AChR has a permissive role in NMDA receptor action in the primate prefrontal cortex, strengthening cognitive functions, thus suggesting a promising combination therapy of these two compounds in clinical settings [151].…”
Section: Type II Pams As a Therapeutic Alternativementioning
confidence: 93%
“…ST-101 (ZSET-1446; Sonexa Therapeutics, San Diego, CA under license from Zenyaku Kogyo, Tokyo) is in Phase II clinical trials for AD since February 2009 and for the treatment of essential tremor since May 2011 (for the structure, see [7]). Combination effects of ZSET1446/ST101 with memantine on cognitive function and extracellular acetylcholine in the hippocampus of rats were described [45]. It was recognized that ST-101 targeted T-type voltage-gated calcium channels in mediating improved cognition in the CNS [46] (Thomson Reuters Pharma, update of October 8, 2013).…”
Section: Drugs Interacting With Ion Channels (Non-receptors)mentioning
confidence: 99%